Bypassing birthing centres for child birth: a community-based study in rural Chitwan Nepal - Rajani Shah (BMC, 2016)
Abstract Background Child delivery in a health facility is important to reduce maternal mortality. Bypassing nearby birthing facility to deliver at a hospital is common in developing countries including Nepal. Very little is known about the extent and determinants of bypassing the birthing centres in Nepal. This study measures the status of bypassing, characteristics of bypassers and their reasons for bypassing. Methods A community-based cross-sectional study was carried out in six rural village development committees of Chitwan district of Nepal. Structured interviews were conducted with 263 mothers who had given birth at a health facility and whose nearest facility was a birthing centre. Descriptive statistics, univariate and multivariable logistic regression analysis were performed. Results More than half of the mothers had bypassed the nearer birthing centres to deliver at hospital. Living in plain area [aOR: 2.467; 95 % CI: 1.005-6.058], higher wealth index [aOR: 4.981; 95 % CI: 2.482-9.999], advantaged caste/ethnicity [aOR: 2.172; 95 % CI: 1.153-4.089], older age [aOR: 2.222; 95 % CI: 1.050-4.703] and first birth [aOR: 2.032; 95 % CI: 1.060-3.894] were associated with higher likelihood of bypassing. Among the reasons of bypassing as reported by the bypassers, lack of operation, video x-ray, and blood test facilities were the most common ones, followed by the lack of medicines/drugs and equipment, lack of skilled service provider, and inadequate physical facilities, among others. Conclusions Quality of service at the birthing centres needs to be given a high consideration to increase their use as well as to ensure an equitable access to the quality care by all.